Exploiting Orientation Information to Improve Range-Based Localization Accuracy - Tomic, Slavisa (2021)
Funding Information: This work supported in part by the Fundação para a Ciência e a Tecnologia under Project IF/00325/2015, Project foRESTER PCIF/SSI/0102/2017, and Project UIDB/04111/2020, and in part by the Universidade Lusófona/ILIND internal project TESLA.